Penerapan Omnibus Law dalam Pembentukan Peraturan Daerah - Eka Nam Sihombing; Srining Widati; Cynthia Hadita (Jurnal Ilmiah Penegakan Hukum, 2020)
The method for the formation of laws and regulations that has become the public spotlight recently is the Omnibus Law method which of course cannot only be applied in the formation of laws alone. It can also be applied in the formation of regional regulations. However, this is not yet an issue that is discussed nationally. The purpose of this study is to answer legal problems related to the application of the omnibus law in the formation of regional regulations so that there is a common viewpoint and become input for stakeholders. The research method used is normative juridical. The results show that the formation of local legislation using the omnibus law method can minimize disharmony of local legislation both vertically and horizontally with PUU.